A conceptual model of nickel content in the bodies of seafood mollusks and their gastrointestinal absorption - Chee, Kong Yap; Wen, Siang Tan; Wan Mohd Syazwan; Noor AzrizalWahid; Nulit, Rosimah; Mustafa, Muskhazli; Abdul Rahman, Mohd Amiruddin; Chee, Wah Yap; Edward, Franklin Berandah; Arai, Takaomi; Wan, Hee Cheng (SciRes Literature LLC, 2022)
There are many biomonitoring studies of nickel in the mollusks, but to understand how the nickel is accumulated in the human body and the health risk posed by the metal is not a straightforward formula. Therefore, the aim of this paper is to draw a conceptual model of nickel content in the bodies of invertebrate mollusks and their gastrointestinal absorption of nickel. This model is useful to understand how nickel accumulation in the tissues of the mollusks could affect the nickel oral ingestion pathways. This conceptual model can shed some light on the mechanisms of nickel that may cause various toxicological risks and target cancer slope formulation in the future.